The Effect of the Hedonic Value of the Online Digital Experience on Brand Advocacy: The Mediating Role of Brand Engagement and the Moderating Role of Digital Experience Satisfaction in Tourism Destinations in Southwest Papua - Idjie, Fince Milha; Maghrifani, Dila (Universitas Muhammadiyah Pontianak, 2026)
Digital technology has transformed how tourists interact with tourism destinations. This study examines the effect of Hedonic Value of the Online Digital Experience on Brand Advocacy, with Brand Engagement as a mediator and Digital Experience Satisfaction as a moderator. Using an explanatory quantitative approach, data from 230 tourists were analyzed using PLS-SEM. The results show that all direct relationships are significant, Brand Engagement partially mediates the relationship, and Digital Experience Satisfaction strengthens the effect on Brand Advocacy. These findings highlight the importance of enjoyable digital experiences in encouraging tourists to become destination advocates.